A lymphodepleted non‐human primate model for the assessment of acute on‐target and off‐tumor toxicity of human chimeric antigen receptor‐T cells. Issue 6 (3rd June 2021) - Yagyu, Shigeki; Mochizuki, Hidemi; Yamashima, Kumiko; Kubo, Hiroshi; Saito, Shoji; Tanaka, Miyuki; Sakamoto, Kengo; Shimoi, Akihito; Nakazawa, Yozo
Abstract: Objectives: Chimeric antigen receptor (CAR)‐T cell therapy possesses the potential to cause unexpected on‐target toxicities that may be life‐threatening. Non‐human primates (NHPs) share considerable structural homology and expression profiles of most proteins with humans and are therefore utilised as an animal model for non‐clinical safety studies. We have developed a lymphodepleted NHP model by conditioning the animals with immunosuppressive chemotherapy designed to simulate clinical practice conditions, to induce transient mixed chimerism before the administration of human CAR‐T cells redirected to target Ephrin type‐B receptor 4 (EPHB4‐CAR‐T cells) to evaluate the toxicity of these cells. Methods: We administered 60 mg m −2  day −1  of fludarabine for 4 days and 30 mg kg −1  day −1  of cyclophosphamide for 2 days intravenously to cynomolgus macaques for lymphodepletion; then, 3.3 × 10 6  kg −1  of non‐transduced or EPHB4‐CAR‐T cells was infused into the macaques, respectively. All macaques were closely monitored and evaluated for potential toxicity for 7 days. Results: Lymphodepletion was successfully achieved on day −1 before T‐cell infusion and persisted over 7 days without severe organ toxicities. A single administration of human EPHB4‐CAR‐T cells did not induce overt organ toxicities, although EPHB4‐CAR‐T cells were activated  in vivo  as evidenced by the elevation in copy numbers of the CAR transgene 24 h after infusion. Conclusion: Although this NHP model is limited for the full evaluation of toxicity of human CAR‐T cells and the conditioning protocol should be further optimised, this lymphodepleted NHP model could be used to assess acute on‐target/off‐tumor toxicities of CAR‐T cells. Abstract : We have investigated the on‐target/off‐target toxicity of CAR‐T cells using a lymphodepleted non‐human primate (NHP) model. We followed the most widely accepted non‐myeloablative lymphodepletion protocol in clinical use for CAR‐T therapy to deplete the lymphocyte counts in the macaques, and lymphodepletion allowed CAR‐T cells to transiently expand and become detectable in the peripheral blood. Our lymphodepleted NHP model could provide new insights into the safety assessment of immune effector cell‐based therapy as the investigational new intervention.